The Level of Effectiveness of TPS and Conventional Methods Judging from Students' Geometry Learning Results Using the N-Gain Test - Triyono, Ageng; Nuary, Rusdi Hamdany; Permatasari, Nisa; Yuni, Yatha; Wibowo, Teguh (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
The low results of student geometry learning require a trial of the think-pair-share method as a replacement for conventional methods. This research aims to: (1) compare the level of effectiveness of applying the think-pair-share method with conventional learning in improving student geometry learning outcomes, and; (2) determine whether or not there is a significant effect from using the two methods. The method used is quasi-experimental with a nonequivalent pretest-posttest control group design involving an experimental group and a control group. Each group consisted of 23 class VII students selected non-randomly from the population. Data was taken using a geometry learning outcomes test instrument. Data were analyzed using the N-Gain Score test, the results of the calculations were converted into interpretation categories for N-Gain effectiveness to be concluded. Research findings: (1) the application of both methods was